STUDIES ON CRITICALLY ENDANGERED GENUS CEROPEGIA FROM WESTERN GHATS OF NASHIK DISTRICT, MAHARASHTRA, INDIA - Madhukar Pandharinath SANGALE; Sanjay Ragho KSHIRSAGAR; Hemendra Prabhakar SHINDE (Journal of Plant Development)
Ceropegia is tuberous herb, mostly found growing on grassy slopes of hills and plateaus. Species of Ceropegia are recognized mostly for its peculiar ornamental and/or medicinal properties. Most species from the genus Ceropegia are included in threatened category because of special requirements in terms of climate and habitat. Earlier studies have indicated that habitat destruction and collecting of tubers for local consumption are the major threats. However; during recent years; their populations have been found declining rapidly due to habitat modifications and anthropogenic pressures like grazing, tourism and trampling, land use changes, etc. Since the majority of the reported Ceropegia species were previously classified as vulnerable or endangered by the IUCN, conservation efforts ought to be pursued in order to slow the rate at which these species are becoming extinct. Present research article deals with taxonomy, flowering and fruiting period, present status, threats of critically endangered Ceropegia species found in and around Western Ghats region of Nashik district. The present study would help in identifying the species habitats and the areas to be prioritized for their conservation.